Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

why does the MVT allow us to conclude that if D(f(x)) = D(g(x)) then f(x) = g(x) + C ???

MIT 18.01 Single Variable Calculus (OCW)
See more answers at
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly


Get your free account and access expert answers to this and thousands of other questions

wat is D

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

im assuming D is differential
Thank you
hey i dont htink thats the way you want it proved tho, with the mean value theorm
go here and watch from time 28:04 mins
or there
I was also wondering the same thing when going through the course. I tried to make up the proof myself, I don't know if it is correct but here it is: MVT says (f(b)-f(a))/b-a = D(f(c)) and (g(b)-g(a))/b-a = D(g(c)) But if we take 'b' as variable(this is my major assumption) over the domain of the functions f and g, we get (f(x)-f(a))/x-a = D(f(x)) and (g(x)-g(a))/x-a = D(g(x)) And we are given D(f(x)) = D(g(x)), so (f(x)-f(a))/x-a = (g(x)-g(a))/x-a => f(x)-f(a) = g(x)-g(a) => f(x) = g(x) + (f(a)-g(a)) => f(x) = g(x) + constant; as ((f(a)-g(a)) is a constant Q.E.D.
You can prove it without MVT: Proof by Contraposition: To prove that p implies q, you can instead attempt to prove NOT q implies NOT p, this is because the two statements are logically equivalent. Thus, if the "NOT" statement is true, then the other statement must be true as well. In this case, p is D(f(x))=D(g(x)) and q is f(x)=g(x)+c This means that NOT p is D(f(x)) =/= D(g(x)) and NOT q is f(x)=/=g(x)+c So lets try to prove NOT q implies NOT p: if f(x) =/= g(x) + C, then by the definition of the derivative, D(f(x)) =/= D(g(x)). Therefore, we have proven our contrapositive, and logically, proven the original.

Not the answer you are looking for?

Search for more explanations.

Ask your own question